If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 24 = 5x + -3 Reorder the terms: 24 + 8x = 5x + -3 Reorder the terms: 24 + 8x = -3 + 5x Solving 24 + 8x = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 24 + 8x + -5x = -3 + 5x + -5x Combine like terms: 8x + -5x = 3x 24 + 3x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 24 + 3x = -3 + 0 24 + 3x = -3 Add '-24' to each side of the equation. 24 + -24 + 3x = -3 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = -3 + -24 3x = -3 + -24 Combine like terms: -3 + -24 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| -2x+6=-3(2x+10) | | 3+(k+3)=6(k-2)+9 | | z^2-14z-13=0 | | 2/5(4x+2)=3(2-2x)+10 | | 6-(m-5)-21=m-11+17 | | 2y+100=2x | | 1/5x+3=-4 | | 18x-4=7x+7 | | 4x+44+6x+36=180 | | 5y=6x+13 | | (3m+4/5)^2 | | 2(8-x)=3x+6 | | 2x+1=6x+13 | | 7x(x)+4x-17=31-30x | | -7x(x)+4x-17=31-30x | | -141-2x=-12x+99 | | -11-2x=-12x+99 | | 2m-3(m+5)-11=2m+6-m | | (12-7)*5+1= | | 4a*3-64a=0 | | 1/2-5x=2 | | 4(x-1)=6(x+3) | | (6x-9)(5x+9)=0 | | 1/4^-2 | | 1/24s^2-150=0 | | 16h=80 | | 2a-22.8=a+1.2 | | x(x-6)=3(x+12) | | 12x+9=17x-8 | | -89+12x=8x+27 | | 9x-9+4x-4=7x+6x-16 | | -3x^2-24x=21 |